การวิเคราะห์แบบไร้เชิงเส้นทางวัสดุของโครงข้อแข็งในระนาบ - ธิติ จุติวิโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
When structures are subjected to loads larger than desired, internal forces may exceed the yield strength of materials. Consequently, nonlinear behavior occurs and induces structural stability and failure characteristics. This research presents an analysis method of planar frames considering materially nonlinear behavior. A computer program is developed by applying the fiber model and spread plasticity to construct the structural element. Static monotonic loading is applied at structural nodes. Solutions to the nonlinear problems are carried out by a displacement control method and a load control method to obtain the load and displacement relationship. Results from case studies are shown that the computer program developed in this research, both stiffness and flexibility method, can predict the materially nonlinear behavior and yields the results with accuracy more than 99% when compared with the exact solution. The stiffness method, which is based on assumed shape functions, needs to refine meshes in order to yield a good result. On the other hand, the flexibility method, which is based on exact force interpolation functions, does not require a large number of elements. However, considering spread plasticity along the element can help improve the accuracy. Applying 7 integration points in each element, each structural member can be modeled using only 1 finite element. Consequently, a remarkable result can be obtained within a short computer time.